Driver head locations: Considerations for head restraint design. (17th November 2018) - Park, Jangwoon; Jones, Monica L. H.; Ebert, Sheila M.; Reed, Matthew P.; Hallman, Jason J.
Abstract: Objective: U.S. FMVSS 202a requires that a vehicle head restraint lie within a specified distance (55 mm) from the physical headform on the head restraint measurement device (HRMD). Smaller values of this distance, known as backset, are frequently associated with improved protection against neck injury in rear impact. In some vehicles, small backsets are also associated with complaints of head restraint interference with drivers' preferred head positions. The objective of this study is to examine head/head restraint distances using data from a lab study of driving posture to provide guidance for safe and comfortable head restraint design. Methods: Head positions were measured for 88 U.S. drivers in a laboratory mockup using a seat from a mid-size sedan. The head restraint was removed to allow measurement of drivers' preferred head locations without interference from the head restraint. Rates of disaccommodation, defined as interference between predicted possible head restraint locations and drivers' preferred head locations, were analyzed at HRMD-referenced backsets of 25, 50, 75, and 100 mm measured at 22° and 25° seat back angles. Results: With HRMD-referenced backsets of 25 mm and 50 mm measured at 25°, the head restraint intersected the preferred head locations of 17.9 and 5.2% of the drivers, respectively. An HRMD-referenced backset measured at 22° produced larger accommodation rates than the same backset measured at 25°. Conclusions: The reported distribution of occupant head positions and the resulting restrictions on comfortable head restraint position at various HRMD-referenced backsets and seat back angles help provide guidance for head restraint design. Knowing the actual mean driver-selected seat back angle for a particular vehicle seat and the model presented in this work, a manufacturer can choose a head restraint location that will have a high likelihood of complying with FMVSS backset requirements while also achieving minimal disaccommodation. The findings in this study support the flexibility in the current FMVSS 202a that permits testing at more upright seat back angles than the 25° originally proposed.